EFFECTS OF POLIDOPAMINE COATING ON POLYPROPILENE MEMBRANE FOR ORGANIC FILTRATION - Mundarti, Sri
EFFECTS OF POLIDOPAMINE COATING ON POLYPROPILENE MEMBRANE FOR ORGANIC FILTRATION By Sri Mundarti NIM: 23017035 (Master’s Program in Chemical Engineering) Organic fouling has become the main limitation in application of ultrafiltration (UF) membrane in drinking water treatment. Surface hydrophilization by polydopamine (PDA) coating can be a promising method to minimize fouling formation. In this work, a simple approach was proposed to modify polypropylene (PP) hollow fiber membrane surface by PDA coating in various solution concentration (1 to 5 g/L). The hydrophilicity of modified PP membrane was characterized by measuring the water contact angle, while the filtration tests were conducted to determine the membrane performances using a model humic solution and peat water as the feed. The water contact angle of PP membrane was decreased from 96o to 78o after coated by 3 g/L of PDA for 1 hour. The modified PP membrane had a porosity of 62% with a pure water flux of 63 L/m2.h and humic acid (HA) rejection of 91%. When the modified PP membrane was used to filter the peat water, the rejection was only 22%. Moreover, highest rejection of HA was achieved over than 95% when the PP membrane surface was coated by 5 g/L of PDA. It might be associated to the lower solubility of organic acid in model solution than in peat water. The flux recovery ratio (FRR) of all coated PP membranes was higher than the uncoated membrane. It showed that the PDA coated membrane had lower fouling tendency compared to the uncoated PP membrane.